THE RELATIONSHIP BETWEEN REFLECTIVE PROCESSES AND THE BELIEF IN CONSPIRACY THEORY DURING THE COVID-19 PANDEMIC - Yarosh, Nina (PSYCHOLOGICAL JOURNAL, 2020)
The article analyses socio-psychological features of the belief in conspiracy theories. The national and foreign approaches to the phenomenon of faith in conspiracy theories as a reaction to the long-term uncertainty are identified. The article emphasized that the spread of conspiracy theories in the modern world is facilitated by the spread of the coronavirus COVID-19 and its recognition as a pandemic. Stressful events can sometimes contribute to the development of an individual’s conspiratorial thinking. The article emphasizes that the spread of such ideas can be contributed by vast amount of free time (because of introduced quarantine measures) and the active use of social networks. Incidentally, all this can stimulate the development of reflexive processes. The article considers the differential model of reflexivity (D. Leontiev, E. Osin), which differentiates positive (systemic reflection) and negative (quasi-reflection, introspection) reflexive processes. The empirical hypothesis of the study was to examine the existence of significant correlations between belief in conspiracy theories and negative reflexive processes. We conducted the empirical study on relations between reflexive abilities and belief in conspiracy theories associated with COVID-19. The features of the respondents’ reflexive abilities during quarantine restrictions were empirically determined. The studied respondents showed mainly quasi-reflection, which led to unfounded fantasies and acted as a form of psychological protection for moving away from an unpleasant situation, the real solution of which is unattainable. Systemic reflection was less developed, which indicated low adaptability to life situations, as well as described the nature of the analysis of situations in which an individual finds him/herself. The respondents had poor ability to outline life situations in all their interacting aspects. The performed study on existence and strength of faith in conspiracy theories points to characteristic manifestations of conspiracy theories. The most popular theory among respondents was the belief that coronavirus infection was a biological weapon and was created deliberately in secret laboratories. The statistical analysis demonstrated a significant two-way relation between quasi-reflection and belief in conspiracy theories.